Alternative kinds of energy in Ukraine and their using - Maksymchuk, Anastasiia; Kovalova, Olena (My University, 2020)
We have a lot of environmental problems in Ukraine. One of the biggest problems is the energy problem. One of the best ways to solve this problem is to use an alternative kind of energy. We can use solar, hydro, and wind energy. Using the alternative energy, allows us to save a lot of energy and save our planet from overuse of resources. В нас багато екологічних проблем в Україні. Однією з найбільших проблем є енергетична проблема. Один з найкращих способів вирішити цю проблему - використовувати альтернативний вид енергії. Ми можемо використовувати сонячну, гідро- та вітрову енергію. Використання альтернативної енергії дозволяє заощадити багато енергії та врятувати нашу планету від надмірного використання ресурсів.
Keywords: альтернативна енергетика; alternative energy; energy sources; solar power; wind power; hydropower; кафедра ділової іноземної мови та міжнародної комунікації; джерела енергії; сонячна енергія; енергія вітру; гідроенергетика